Command Directive Illocutionary Act Found in “Hobbs & Shaw” Movie - I Kadek Rama Dwi Jayantha; Maharani, Putu Devi; Permana, I Putu Andri (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2022)
This study entitled “Command Directive Illocutionary Acts found in Hobbs & Shaw Movie” It aims for finding out the command directive illocutionary acts and the context of situation of directive illocutionary acts utterance expressed by the main characters. The command directive illocutionary acts are discussed using the theory of directive illocutionary acts proposed by Kreidler (1998: 189-190) and the context of situation is discussed using theory of the context of situation proposed by Halliday and Hasan (1985: 12). In collecting the data, the writer watched the movie and marked the utterances that contain command directive illocutionary acts in the movie script. The method used in analyzing data was descriptive qualitative method. The writer classified the data based on the sentence structure of the command directive illocutionary act and then analyzes the context of the situation. In presenting the findings, formal and informal methods are used. The formal method is used to show the percentage of sentence structure of command directive illocutionary acts using table and the informal method is used to explain the data descriptively through words. In this study, 31 data were found regarding illocutionary acts of directive orders.